2020
DOI: 10.21307/jofnem-2020-043
|View full text |Cite
|
Sign up to set email alerts
|

Differences in parasitism of root-knot nematodes (Meloidogyne spp.) on oilseed radish and oat

Abstract: Oilseed radish and oat are cool season annual crops that are potentially used as "trap" or "biofumigant" crops for the suppression of plantparasitic nematodes in soil. Cultivars of oilseed radish (Carwoodi, Cardinal, Final, Image, Concorde, Control, Eco-Till, Karakter and Cannavaro), white (Tachiibuki) and black (Pratex) oats were evaluated for their ability to reduce reproduction of three root-knot nematode species: Meloidogyne javanica, M. incognita race 3, and M. arenaria race 1. Nematode penetration and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Phylogenetic studies of nematode genome have provided evidences supporting the evolution of parasitism on various occasions during evolution in plantparasitic nematodes [6]. Similar trend was followed by animal parasitic nematodes as well [7][8][9]. This observation strongly suggests acquisition of favourable gene during evolution of nematodes [10,11].…”
Section: Introductionmentioning
confidence: 63%
“…Phylogenetic studies of nematode genome have provided evidences supporting the evolution of parasitism on various occasions during evolution in plantparasitic nematodes [6]. Similar trend was followed by animal parasitic nematodes as well [7][8][9]. This observation strongly suggests acquisition of favourable gene during evolution of nematodes [10,11].…”
Section: Introductionmentioning
confidence: 63%
“…While a RF less than one is, by this de nition, resistant, maintaining nematode populations at or near the initial load is not satisfactory for growers. Ideally, a next-generation sweetpotato variety would be so highly resistant as to be considered a non-host (RF < 0.1), as de ned by Hamidi and Hajihassani (2020). The TB population has demonstrated that this level of resistance is attainable in sweetpotato through a single cross with a resistant parent.…”
Section: Bioassaymentioning
confidence: 99%